Garden of expression [compact disc] - Lovano, Joe (ECM, 2021)
Joe Lovano's debut, Trio Tapestry, was one of 2019's most talked-about releases. Their concept is taken to the next level on Garden of Expression. Lovano is a saxophonist who plays with exceptional sensitivity. Carmen Castaldi's space-conscious approach to drumming further refines his improvisational understanding. The trio is also a wonderful context for Marilyn Crispell's solos and counter melodies. The album was recorded at the Auditorio Stelio Molo RSI and produced by Manfred Eicher.